Bullying in Schools: Are Pre-Service Teachers Confident to Address This? - Maynes, Nancy; Mottonen, Anna-Liisa (Alberta Journal of Educational Research, 2018)
Research suggests that, due to a lack of confidence, pre-service teachers feel inadequately prepared to deal with bullying situations. Confidence has been demonstrated to be a function of knowledge related to the concept being considered. To improve pre-service teachers’ confidence to deal with bullying incidents, factors influencing their confidence levels must be identified, including those related to their teacher preparation programs. The primary aim of this study was to examine whether pre-service teachers’ self-reported confidence in their ability to respond appropriately to bullying situations depended on which teacher preparation program (consecutive vs. concurrent) they completed. Additionally, other factors that may be related to confidence, such as gender, division of instruction, and variables such as type of bullying, were examined. Participants included 183 pre-service teachers with a mean age of 23 years, the majority of whom were female, who had completed or were completing either the concurrent or consecutive teacher preparation program at a Northern Ontario university. Self-reported confidence in ability to respond appropriately to suspected bullying incidents was assessed using an online Likert style questionnaire. Results demonstrated that, with respect to confidence to respond appropriately to suspected bullying, consecutive program participants reported higher confidence than concurrent program participants, with non-significant variations in perceptions across genders of the teachers and/or the divisions for which they were prepared in their teacher accreditation programs, and surprisingly high levels of confidence in this area across both program models were demonstrated. This finding has implications for teacher training, as evidence suggests that teachers may benefit from training to handle bullying that is designed for their experience level and previous research shows that new teachers may identify high levels of confidence even when they may lack the knowledge that should support their self-perceptions. La recherche porte à croire que les enseignants en formation manquent de confiance et donc se sentent mal préparés pour faire face aux situations d’intimidation. Il a été démontré que la confiance est fonction de connaissances liées au concept en question. Afin de donner aux enseignants en formation la confiance de gérer les incidents d’intimidation, il faut identifier les facteurs qui influencent leur confiance, y compris ceux qui découlent des programmes de préparation des enseignants. L’objectif principal de cette étude était d’examiner dans quelle mesure la confiance de gérer de façon appropriée les situations d’intimidation, telle qu’indiquée par les enseignants en formation dans une auto-évaluation, était liée au programme de préparation (consécutif ou concomitant) qu’ils avaient complété. D’autres facteurs pouvant également jouer un rôle dans leur niveau de confiance, comme le genre, la répartition de l’enseignement et le type d’intimidation, ont également été étudiés. L’étude avait comme participants 183 enseignants en formation dont l’âge moyen était de 23 ans. La majorité était des femmes et elles suivaient le programme consécutif ou concomitant de formation des enseignants dans une université dans le Nord de l’Ontario. Un questionnaire en ligne reposant sur des échelles de style Likert a fourni les données de l’auto-évaluation de la confiance à gérer de façon appropriée les situations d’intimidation. Les résultats indiquent que les participants au programme consécutif avaient plus confiance à confronter des situations d’intimidation que les participants au programme concomitant. Les variations entre les hommes et les femmes, et parmi les répartitions d’enseignement, n’étaient pas significatives. Le niveau de confiance auto-déclaré par tous les participants était étonnamment élevé. Ces constatations ont des implications pour la formation des enseignants puisque les études indiquent que, d’une part, les enseignants pourraient profiter d’une formation qui vise la gestion de l’intimidation et qui est adaptée à leur niveau d’expérience et que, d’autre part, il se peut que les nouveaux enseignants indiquent un niveau élevé de confiance alors qu’ils n’ont pas les connaissances pour appuyer leur auto-évaluation.